Impact of patient training patterns on peritonitis rates in a large national cohort study - Figueiredo, Ana Elizabeth; Moraes, Thyago Proenca de; Bernardini, Judith; Poli-de-Figueiredo, Carlos Eduardo; Barretti, Pasqual [UNESP]; Olandoski, Marcia; Pecoits-Filho, Roberto (Oxford Univ Press, 2015)
Background. Ideal training methods that could ensure best peritoneal dialysis (PD) outcome have not been defined in previous reports. The aim of the present study was to evaluate the impact of training characteristics on peritonitis rates in a large Brazilian cohort.Methods. Incident patients with valid data on training recruited in the Brazilian Peritoneal Dialysis Multicenter Study (BRAZPD II) from January 2008 to January 2011 were included. Peritonitis was diagnosed according to International Society for Peritoneal Dialysis guidelines; incidence rate of peritonitis (episodes/patient-months) and time to the first peritonitis were used as end points.Results. Two thousand two hundred and forty-three adult patients were included in the analysis: 59 +/- 16 years old, 51.8% female, 64.7% with <= 4 years of education. The median training time was 15 h (IQI 10-20 h). Patients were followed for a median of 11.2 months (range 3-36.5). The overall peritonitis rate was 0.29 per year at risk (1 episode/41 patient-months). The mean number of hours of training per day was 1.8 +/- 2.4. Less than 1 h of training/day was associated with higher incidence rate when compared with the intervals of 1-2 h/day (P = 0.03) and > 2 h/day (P = 0.02). Patients who received a cumulative training of > 15 h had significantly lower incidence of peritonitis compared with < 15 h (0.26 per year at risk versus 0.32 per year at risk, P = 0.01). The presence of a caregiver and the number of people trained were not significantly associated with peritonitis incidence rate. Training in the immediate 10 days after implantation of the catheter was associated with the highest peritonitis rate (0.32 per year), compared with training prior to catheter implantation (0.28 per year) or > 10 days after implantation (0.23 per year). More experienced centers had a lower risk for the first peritonitis (P = 0.003).Conclusions. This is the first study to analyze the association between training characteristics and outcomes in a large cohort of PD patients. Low training time (particularly < 15 h), smaller center size and the timing of training in relation to catheter implantation were associated with a higher incidence of peritonitis. These results support the recommendation of a minimum amount of training hours to reduce peritonitis incidence regardless of the number of hours trained per day.
Keywords: Education; Nursing; Peritoneal dialysis; Peritonitis; Training